1990
DOI: 10.7326/0003-4819-112-10-758
|View full text |Cite
|
Sign up to set email alerts
|

L-Tryptophan Ingestion Associated with Eosinophilic Fasciitis but Not Progressive Systemic Sclerosis

Abstract: L-Tryptophan use can lead to eosinophilic fasciitis whereas it does not appear to cause classic scleroderma. The disease process does not automatically remit after discontinuation of L-tryptophan-containing products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(19 citation statements)
references
References 7 publications
0
17
0
2
Order By: Relevance
“…17 Trauma has been reported as a cause and accepted for workers' compensation in France. 18 L-tryptophan is known to be associated with EMS (eosinophilia myalgia syndrome), 19,20 however, 8 patients with a history of L-tryptophan ingestion have been reported in 1990 to have EF. 19 Interestingly, L-tryptophan became available in the United States in 1974, the year in which EF was first described.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Trauma has been reported as a cause and accepted for workers' compensation in France. 18 L-tryptophan is known to be associated with EMS (eosinophilia myalgia syndrome), 19,20 however, 8 patients with a history of L-tryptophan ingestion have been reported in 1990 to have EF. 19 Interestingly, L-tryptophan became available in the United States in 1974, the year in which EF was first described.…”
Section: Discussionmentioning
confidence: 99%
“…18 L-tryptophan is known to be associated with EMS (eosinophilia myalgia syndrome), 19,20 however, 8 patients with a history of L-tryptophan ingestion have been reported in 1990 to have EF. 19 Interestingly, L-tryptophan became available in the United States in 1974, the year in which EF was first described. 21 Eosinophilia myalgia syndrome (EMS) is a multisystem toxin-induced disorder, and 98% of all patients have a history of ingesting L-trytophan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soon reports of eosinophilia myalgia syndrome [27] and eosinophilic fasciitis [28,29], associated with the ingestion of L-tryptophan were received. Although initially linked to a contaminant in a product made by a single manufacturer [30], authors soon reported the same reaction to L-tryptophan produced by other manufacturers [31].…”
Section: The Kynurenine Pathwaymentioning
confidence: 99%
“…Comparable results were found by Freundlich ct al. [13], In cooperation with the German self-aid group 'Sclero derma'. 137 PSS patients were questioned concerning their E-tryptophan use before the onset of their disease.…”
mentioning
confidence: 99%